2018
DOI: 10.1177/0972150918779165
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Venture Capital Investment on Firm Performance: An Indian Evidence

Abstract: We evaluate the monitoring and certification hypotheses associated with venture capital (VC) investors involved with Indian listed firms having the potential to influence firm performance. Empirical results of our study do not support monitoring and certification hypotheses associated for VC investors involved in publicly listed firms in India. On the other hand, we find the evidence of value erosion due to the presence of VC investors. The negative effect is justified through the opportunistic behaviour of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The coefficients of other variables are insignificant. to increase economic efficiency are limited (Katti & Raithatha, 2018). Owners of a company can use concentrated ownership as a corporate governance mechanism to reduce agency costs.…”
Section: Endogenous Relationship Between Oc and Market Performance (T...mentioning
confidence: 99%
See 1 more Smart Citation
“…The coefficients of other variables are insignificant. to increase economic efficiency are limited (Katti & Raithatha, 2018). Owners of a company can use concentrated ownership as a corporate governance mechanism to reduce agency costs.…”
Section: Endogenous Relationship Between Oc and Market Performance (T...mentioning
confidence: 99%
“…The interests of minority shareholders may not be represented by large shareholders and therefore, minority shareholders may be expropriated. In emerging markets like India, the laws for shareholders’ protections are weak and thus, the resources to increase economic efficiency are limited (Katti & Raithatha, 2018). Owners of a company can use concentrated ownership as a corporate governance mechanism to reduce agency costs.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…As Seet et al (2020) suggested, the internal value of entrepreneurial firms is positively related to entrepreneurial attitude. Indian evidence from Katti and Raithatha (2020) reveal a negative effect when opportunistic investors have a favorable exit option from their portfolios. Thus, possibly more optimistic entrepreneurs and VC investors are careless about firm performance in developing countries like China and India.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Raghupathy and Thillairajan (2015) compared the performances of VC-backed IPOs with that of non-VC backed IPOs, and concluded that VC-backed IPOs exhibited superior performance. Katti and Raithatha (2018) presented the evidences for value erosion when VCs exhibit the opportunistic behavior of exiting through the easy route of secondary market when the venture is expected to underperform. Their study focused on the returns generated at exit than on the exit routes adopted.…”
Section: Hypotheses Developmentmentioning
confidence: 99%